Management of Perforating Idiopathic Internal Root Resorption - Abdullah, Dalia; Hussein, Farah Eziana; Abd Ghani, Huwaina (Iranian Endodontic Journal, 2017)
This case report describes the endodontic treatment of an idiopathic perforated internal root resorption. A 24-year-old male Malay patient presented with internal root resorption of two of his anterior teeth. The medical history was non-contributory and he had no history of traumatic injury or orthodontic treatment. Cone-beam computed tomography (CBCT) determined the nature, location and severity of the resorptive lesion. Non-surgical root canal treatment of tooth #22 and combined non-surgical and surgical approach for tooth #11 were carried out using mineral trioxide aggregate (MTA) as the filling material. The clinical and radiographic examination three years after completion of treatment revealed evidences of periapical healing. The appropriate diagnosis and the treatment of internal root resorption allowed good healing of these lesions and maintained the tooth in function for as long as possible. Keywords: Cone-Beam Computed Tomography; Idiopathic; Internal Root Resorption; Mineral Trioxide Aggregate